MOTIVASI MENGHAFAL AL QUR’AN SISWA MTS ASSALAM NAGA BERALIH - Siti Aisyah (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
The aim of this research is to find out the motivation for memorizing the Al Qur'an of MTS Assalam Naga Beralih students and what the obstacles are and the solutions. The method used in this research is a field study approach, using qualitative research, as primary data in this research students' memorization motivation and secondary data for Tahfizh teachers, data validity is carried out by source triangulation, namely observations and interviews which are then analyzed descriptively. The results of this research show that the motivation for memorizing the Al Qur'an for MTS Assalam Naga Beralih students is carried out by means of motivation in memorizing the Al Qur'an, support from parents, and student intelligence. The obstacles experienced by students are: students' lack of discipline, environment, many tasks that must be done, inappropriate time management, and health. The solution is carried out by evaluating students' memorization of the Qur'an, supervision by the tahfizh teacher regarding students' memorization of the Qur'an and prizes.